Effect of Need, Easy, and Trust on the Intensity of Using the Mobile Health Application to Conduct a Laboratoty Examination: (Case Study on Pramita Lab Surabaya Patients) - Mochammad Baihaqi; Denpharanto Agung Krisprimandoyo (International Journal of Review Management Business and Entrepreneurship (RMBE), 2021)
This study aims to analyze the influence of need, convenience and trust on the intensity of using the mobile health application to perform laboratory examinations on Pramita Lab Surabaya patients. This research is important because the intensity of the use of the mobile health application is influenced by the needs, convenience and trust of patients in the mobile health application. The sample in this study were all 108patients using the mobile health application at Pramita Lab Surabaya. The research design used is quantitative research with a descriptive approach with an emphasis on theory testing through measurement of research variables through distributing research questionnaires. The distribution of research questionnaires was carried out using probability sampling techniques. The analysis technique in this study is to use multiple linear regression analysis with the help of SPSS 20.0 software. The results showed that the variables of need, convenience and trust had a positive and significant effect simultaneously on the intensity of using the mobile health application in patients at Pramita Lab Surabaya. The result also show that there is a positive and significant influence on the need, convenience and trust on the intensity of using the mobile health application by patients at Pramita Lab Surabaya.